GENESIS OF LEGAL REGULATION OF WOMEN'S LABOR IN UKRAINIAN LANDS - Tisetska, A. (Київський національний університет імені Тараса Шевченка, 2019)
The article analyzes the prerequisites for the birth and development of legal regulation of women's labor in Ukrainian lands. The genesis of the genesis of legal regulation of women's labor in the territory of present Ukraine has been determined. The content and meaning of each stage are outlined. Their features are outlined. The analysis of the basic normative legal acts is carried out and the following features of the legal regulation of women's work in the period from 1918 to 1953 are highlighted: imperative - this feature is revealed through the use of the imperative method for the legal regulation of women's labor; centrality - this feature most clearly manifested itself in labor relations, since even the smallest issues had to be first addressed at the level of line ministries; declarative - means norms that do not contain a specific rule of conduct, but defines the goals, objectives, principles of particular branches of law, legal institutions, subject, form and means of legal regulation; low level of legal technique - different types of legal technique play the role of organizing and constructing legal material, create conditions for rationalization of legal activity, for optimization of the process of legal ordering of public relations. The following features of legal regulation of women's rights from 1953 to 1991 are also distinguished on the basis of normative legal acts: progressiveness - this feature is manifested through both through the establishment of new legal norms and through restoration; imbalance, because the balance of interests is at the same time the foundation, the inner core, the necessary condition and the path to social consensus; etrocity - the domination of the state in all spheres of society, the "power of power."

У статті проаналізовано передумови зародження та розвитку правового регулювання праці жінок на українських землях. Визначено етапізацію генезису правового регулювання праці жінок на території нинішньої України. Окреслено зміст і значення кожного із етапів. Окреслено їх особливості. Проведено аналіз основних нормативно-правових актів та виділено наступні особливості правового регулювання праці жінок у період з 1918 по 1953 роки: імперативність - дана ознака розкривається через використання для правового регулювання праці жінок саме імперативного методу; централізованість – дана ознака найбільш яскраво проявляла себе у трудових відносинах, оскільки навіть найменші питання повинні були спершу вирішенні на рівні профільних міністерств; декларативність – розуміються  норми, що не містять конкретного правила поведінки, а визначають цілі, завдання, принципи окремих галузей права, правових інститутів, предмет, форми і засоби правового регулювання; низький рівень юридичної техніки –  різні види юридичної техніки відіграють роль організовуючого і конструюючого правового матеріалу, створюють умови для раціоналізації юридичної діяльності, для оптимізації процесу правового впорядкування суспільних відносин. Також на основі нормативно-правових актів виділено наступні особливості правового регулювання прав жінки у період із 1953 по 1991 рік: прогресивність – дана ознака проявляється через як через встановлення нових правових норм, так й через відновлення; розбалансованість, тому що баланс інтересів – це водночас фундамент, внутрішній стрижень, необхідна умова й шлях до суспільного консенсусу; етакратичність – панування держави в усіх сферах життєдіяльності суспільства, «влада влади».
ГЕНЕЗИС ПРАВОВОГО РЕГУЛЮВАННЯ ПРАЦІ ЖІНОК НА УКРАЇНСЬКИХ ЗЕМЛЯХ
Keywords: genesis; legal regulation of labor; women's labor; gender equality; labor activity.; генезис; правове регулюваня праці; праця жінок; гендерна рівність; трудова діяльність.